ANALISIS LAJU DAN BESARNYA VOLUME INFILTRASI PADA BERBAGAI TUTUPAN LAHAN DI DAERAH ALIRAN SUNGAI (DAS) MALUKA - Akhmad Hidayat; Badaruddin Badaruddin; Ahmad Yamani (Universitas Lambung Mangkurat, 2020)
Forests with canopy layers hold back the strength caused by precipitation in the form of water droplets, while the litter layer and various other understorey plants will be useful to increase soil infiltration capacity, so.that the amount of surface flow can.be.reduced. The infiltration rate in a location will be different from the other locations, depending on various factors such as soil texture, organic.matter, soil structure, soil.water.content, soil porosity which will affect the storage and availability of water in the soil and run of . The infiltration rate study is intended to find out the speed and magnitude of the entry or absorption of water vertically into the body of the soil. This.research was.conducted from February to April 2018 including preparation, data collection and report preparation activities in the Maluka Watershed in South Kalimantan. The purpose of this study was to analyze the rate of infiltration in various land cover in the Maluka watershed and analyze the amount of infiltration volume in various land cover in the Maluka watershed. The results of this study indicate that the highest infiltration rate in secondary forest is 5.696 mm / hour and the lowest infiltration in reeds is 0.234 mm / hour. While the highest value of infiltration volume in mixed gardens was 3.151 mm³, while the lowest infiltration volume was in Imperata 0.123 mm³.Keywords: Infiltration; Maluka; watershed